2020
DOI: 10.1016/j.heliyon.2020.e03707
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-FDG PET/CT in the detection of occult malignancy in patients with dermatomyositis

Abstract: The aim of this study was to evaluate whether whole-body 18 F-FDG PET/CT imaging can offer a standard option searching for underlying malignancy in DM patients. Methods: Seventy-five patients diagnosed with DM were referred to our department for whole-body 18 F-FDG PET/ CT to determine whether the patients suffered from malignant tumor. All PET images were analyzed by two experienced nuclear medicine physicians separately. Results: According to the 18 F-FDG PET/CT results, 19 patients were suspected to suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The rash can be itchy and painful. The reported rate of occurrence of malignant neoplasms in patients with DM is 15–30% [ 39 ]. Dysphagia occurs in 10–20% of patients.…”
Section: Classification Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…The rash can be itchy and painful. The reported rate of occurrence of malignant neoplasms in patients with DM is 15–30% [ 39 ]. Dysphagia occurs in 10–20% of patients.…”
Section: Classification Of Pdmentioning
confidence: 99%
“…Except for the patients who had been treated for DM lesions, all the patients concomitantly showed FDG uptakes predominantly in the proximal muscles. One of the previous studies showed FDG-avid various malignant neoplasms in 17 (22%) patients among the total of 75 DM patients [ 39 ]. Another study showed FDG-avid various malignant neoplasms in 7 (12%) patients among the total of 55 DM patients [ 36 , 41 ].…”
Section: Classification Of Pdmentioning
confidence: 99%
“…Therefore, more efficient screen method for example positron emission tomography-computed tomography (PET-CT) might contribute to early detection of primary tumor. Clinicians need to be vigilant when they encounter patients who manifest as internal diseases such as stroke [ 6 , 7 , 8 , 9 ], thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. As occult NSCLC might be the fundamental cause of these non-cancer-related symptoms, the more refined examinations should be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Occult lung cancer, defined as the presence of malignant tumor cells in bronchial washing or sputum but demonstrated no tumor evidence by imaging [ 1 , 2 ], often manifests as metastasis diseases [ 3 , 4 , 5 ] or other internal diseases such as stroke [ 6 , 7 , 8 , 9 ], venous thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. When these patients develop apparent non-cancer-related symptoms, the vast majority may have already progressed to an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…The database search identified 252 records found and 236 records were excluded after title/abstract screening and full-text content because those did not provide any relevant information on the topic of this review (Figure 1). Sixteen articles were eligible for a more detailed description in this review (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Literature Search Study and Patient Characteristicsmentioning
confidence: 99%